Pupil light reflex in young elite athletes: autonomic nervous system activity and viscoelastic properties - Giovannangeli, Cyril J. P.; Borrani, Fabio; Broussouloux, Olivier; Maurelli, Olivier; Schmitt, Laurent; Candau, Robin B. (Frontiers in Physiology, 2024)
Introduction: The pupil light reflex (photomotor reflex) has a duration of 3.5 s and is a highly reproducible measurement. Conventionally, the autonomic nervous system (ANS) activity evaluated by this reflex does not consider the viscoelasticity of the iris muscles. This study aims to detect differences in reflex autonomic activity in a supine position with parameters derived from the Kelvin-Voigt viscoelastic model in two distinct groups of elite athletes. Method: Groups formed using a dendrogram analysis based on basal autonomic activity assessed with heart rate variability. Heart rate variability was measured, and the photomotor reflex was modeled. Results: The model showed a high degree of adjustment to the photomotor reflex (r2 = 0.99 ± 0.01). The impulse 3, an indicator of reflex sympathetic activity, revealed a significantly higher activity (ρ ≤ 0.05) in the [sympa/para]+ group compared to the [sympa/para]⁻ group. This result was further supported by a greater relative total redilation amplitude (ρ ≤ 0.05) and a shorter duration of 75% redilation (ρ ≤ 0.01). Finally, the relative total redilation amplitude exhibited a significant correlation with the linear stiffness constant (ρ ≤ 0.001) and the maximum redilation speed with restoring force (ρ ≤ 0.001). Discussion: These results indicate that (i) the photomotor reflex can detect an alteration of the reflex autonomic activity specific to each of the two branches of the ANS (ii) the viscoelastic properties of the iris muscles play a significant role in the energy storage-restitution mechanisms during the photomotor reflex. This approach could allow athletes to benefit from reduced time spent in the analysis of ANS activity, potentially making it an almost daily and automated process.